2016
DOI: 10.1002/aenm.201600137
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Aluminum‐Ion Battery: Al/AlCl3‐[EMIm]Cl/Ni3S2@Graphene

Abstract: may offer noteworthy cost saving and safety improvement compared to its counterparts. Additionally, aluminum has a very negative redox potential (≈1.676 V vs standard hydrogen electrode (SHE)) and a small electrochemical equivalent (0.336 g Ah −1 ), which make it one of the ideal elements for rechargeable batteries. However, the previous efforts have encountered numerous issues over the past few years, such as the cathode material disintegration, [12,14] low discharge voltage, [8] capacitive behavior without d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
313
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 392 publications
(341 citation statements)
references
References 34 publications
12
313
1
9
Order By: Relevance
“…[67] Similar behaviors could also be observed for Ni 3 S 2 and CuS. [10,12,13,17,[64][65][66][67] Although it is reported that V 2 O 5 delivers specific capacity of 273 mAh g À1 ,i ti sb asically attributed to the side reactions. [37] None of the other cathodes could attain such high specific capacity nor sustain such high current rate.…”
Section: Graphene Versus Other Cathode Materials In Al-ion Cellssupporting
confidence: 55%
See 2 more Smart Citations
“…[67] Similar behaviors could also be observed for Ni 3 S 2 and CuS. [10,12,13,17,[64][65][66][67] Although it is reported that V 2 O 5 delivers specific capacity of 273 mAh g À1 ,i ti sb asically attributed to the side reactions. [37] None of the other cathodes could attain such high specific capacity nor sustain such high current rate.…”
Section: Graphene Versus Other Cathode Materials In Al-ion Cellssupporting
confidence: 55%
“…[10-13, 17, 36, 41-43, 46, 47, 49, 50, 64-67] Indeed, most of the cathodes, irrespective of compositions,d isplay am iserable discharge voltage plateau at approximately 0.5-0.6 V( vs. Al). [13,65] Graphene has the ability to deliver specific capacities as high as 148 mAh g À1 (at current density of 2Ag À1 ). [67] Similar behaviors could also be observed for Ni 3 S 2 and CuS.…”
Section: Graphene Versus Other Cathode Materials In Al-ion Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other side, the XPS spectra of sulfur present a similar shift in the pristine, discharged, and charged states. [7,20,24,26,27] It is noted that this is the first time to find the variations of metallic and sulfur valence state in one AIBs system. [20] Similarly, after charging, the spectra of sulfur recovered to the pristine state with a higher binding energy increasing, revealing that a reversible reaction increases the valence state of sulfur.…”
mentioning
confidence: 77%
“…More information of those aqueous AIBs could be found in the recent elaborated review by Elia et al [88] AIBs in non-aqueous electrolytes have attracted much more attention in recent years because of the higher working voltage as well as higher energy density. [92] Typically, the non-aqueous electrolytes possess a general formula of MCl-AlCl 3 (M + = Li + , Na + , K + , or organic cations like pyrrolidinium or imidazolium). These electrolytes are defined to be basic, neutral or acid when the ratio of MCl/AlCl 3 >1, = 1, and <1, respectively.…”
Section: Al-ion Batteries and Al-based Dual-ion Batteriesmentioning
confidence: 99%